Low-Profile Planar Ultrawideband Modular Antenna Array Loaded With Parasitic Metal Strips - Wang, Haotong; Qu, Shi-Wei; Yang, Shiwen; Hu, Jun (IEEE transactions on antennas and propagation, 2023)
A low-profile dual-polarized planar ultrawideband modular antenna (PUMA) array is proposed in this article. The overall profile is as small as 11.4 mm ( 0.228λ _{high} , where λ _{high} is the free-space wavelength at the highest operating frequency) based on element sizes 25×25 mm 2 ( 0.5× 0.5λ _{high}^{2} ) and a large operating frequency bandwidth achieved by loading lossless parasitic metal strips between the dipole patches and the ground plane. The loop-mode resonance that causes deterioration of the port isolation around the lowest operating frequency is comprehensively analyzed and suppression methods are proposed. To further reduce the overall profile, a metasurface-based wide-angle impedance matching (MS-WAIM) layer is introduced. The surface waves guided by the MS-WAIM layer during wide-angle scanning in H-plane are suppressed by cutting properly-sized square holes at critical positions. The calculated results show that the proposed infinite array can scan up to ±60° in E-/H-planes with active voltage standing wave ratios (VSWRs) below 2.9 within 2-6 GHz and orthogonal port isolations beyond 20 dB. A 12×11 array prototype is fabricated and reasonable agreement is achieved between the calculated and measured results.